Growth Rate of Coral Transplantation of Acropora formosa in Tidung Island, Kepulauan Seribu Regency, Province of DKI Jakarta - Anma Hari Kusuma; Taslim Arifin; Bavo Wahyu Kusumantoro (Jurnal Biologi Tropis, 2023)
Coral reefs are typical tropical ecosystems that have an important role but are vulnerable to damage. Corals need a long time to recover. One effort to accelerate the growth rate of coral reefs is coral transplantation. This research was conducted from June to July 2022. The research location was on Tidung Island, Thousand Islands Regency, DKI Jakarta. The results showed that the physico-chemical conditions of the waters in general were still within the range of quality standards for marine biota, especially for coral reef ecosystems. the recorded survival percentage was 100%. The growth of coral types tends to increase with height gains ranging from 27-40 cm/week. Coral growth rate ranged from 0,01-0,02 cm/week. Overall the coral transplantation of A. Formosa carried out on Tidung Island can be said to be successful because the water conditions on Tidung Island are suitable for supporting coral transplantation activities.